2009
DOI: 10.1111/j.1365-3059.2009.02039.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggressiveness and its role in the adaptation of plant pathogens

Abstract: Aggressiveness, the quantitative component of pathogenicity, and its role in the adaptation of plant pathogens are still insufficiently investigated. Using mainly examples of biotrophic and necrotrophic fungal pathogens of cereals and Phytophthora infestans on potato, the empirical knowledge on the nature of aggressiveness components and their evolution in response to host and environment is reviewed. Means of measuring aggressiveness components are considered, as well as the sources of environmental variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
282
4
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(306 citation statements)
references
References 121 publications
7
282
4
13
Order By: Relevance
“…This Asiatic species has been previously characterized as suppressing sporulation while reacting with strong necrosis [4,33]. Despite this, it has been reported that stronger necrotic reaction correlates to higher susceptibility in crosses of V. vinifera with V. amurensis [14]. This shows that hosts with stronger resistance might block the sporulation of the pathogen without showing necrosis, which was the case for A. japonica in the present study.…”
Section: North American and Asiatic Speciesmentioning
confidence: 42%
See 2 more Smart Citations
“…This Asiatic species has been previously characterized as suppressing sporulation while reacting with strong necrosis [4,33]. Despite this, it has been reported that stronger necrotic reaction correlates to higher susceptibility in crosses of V. vinifera with V. amurensis [14]. This shows that hosts with stronger resistance might block the sporulation of the pathogen without showing necrosis, which was the case for A. japonica in the present study.…”
Section: North American and Asiatic Speciesmentioning
confidence: 42%
“…In our previously published system [7], a set of six host genotypes (two North American species, one European and three commercially used cultivars) was developed to achieve an improved assessment of strain diversity of the oomycete. In the present study, we broaden the characterization system by including The development of necrosis on a specific host reveals the presence of resistance genes [12][13][14] and the level of sporulation achieved by a strain is related to its aggressiveness [15]. Conventional evaluation systems used on P. viticola based on the amount of sporangia do not consider the necrotic reaction of the plant [16][17][18] or evaluate it in combination with the sporulation [13,19].…”
Section: The Characterization Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenicity may be evaluated in many ways such as infection efficiency, latent period, sporulation rate, infectious period or lesion size (PARIUAD et al, 2009). By measuring lesion progress on stems over time, OttoHanson et al (2011) found that S. sclerotiorum isolates collected from dry bean fields in Minnesota were more aggressive than isolates from Nebraska, Michigan and Washington, whereas California isolates were less aggressive than those collected from all other bean production locations.…”
Section: Introductionmentioning
confidence: 99%
“…Where trade‐offs exist between infectivity and other traits that affect pathogen fitness (e.g., spore production; Villaréal & Lannou, 2000; Thrall & Burdon, 2003; Pariaud et al., 2009; Peyraud, Cottret, Marmiesse, Gouzy, & Genin, 2016), theory predicts that regular rotation of cultivars carrying different resistance genes will select against pathogens carrying unnecessary infectivity. However, this may at least partly depend on the initial composition of pathogen populations and whether there are gametic disequilibria (Brown, 1994; Brown & Wolfe, 1990; Hovmøller, Munk, & Østergård, 1993; Kolmer, 1993).…”
Section: Introductionmentioning
confidence: 99%